Effect of exposure time, cell concentration and culture age on the microbial adhesion of staphylococcus aureus and saccharomyces cerevisiae on the glass surface - Raudhah, Ahmad Shupi (2014)
This paper reveals the behaviour of the adhesion of Staphylococcus aureus (S. aureus) and Saccharomyces cerevisiae (S. cerevisiae) on the glass surface with respect to the exposure time, the cell concentration and culture age. Therefore, this study was carried out to investigate the mechanism of microbial adhesion based on the exposure time, cell concentration and culture age, so that further measures can be taken either to influence or to prevent the adhesion of microorganism. In order to investigate effect of exposure time on the adhesion process, the experiments were carried out for 24 hours and sampling was done at 4 h, 8 h, 12 h and 24 h of intervals. At each sampling time, glass slide was examined under the light microscope for determination of the numbers of cell attached per square area. Besides that, the absorbance and the colony forming unit (CFU) were also measured. Based on the result obtained, the absorbance for S. cerevisiae and S. aureus decreased with increasing exposure time with lowest OD reading was obtained at 24 hours, 0.911 and 0.827, respectively indicating a reduction by 8.9 % and 17.3 % from initial reading of 1.000. The OD reduction of cell suspension occurred because the bacteria were attached on glass surfaces and the degree of attachment increased with exposure time. This reading was supported by analysis of the colony forming unit (CFU) count, where the initial reading of CFU for S. cerevisiae was at 16 x1011 CFU/ml and dropped to 10.3 x1011 CFU/ml at the end of the experiment whereas for S. aureus the CFU reading reduced from 317 x 1011 CFU/ml to 115.7 x 1011 CFU/ml. On the other hand, the effect of varying the cell concentration on the degree of adhesion was compared by using cell concentration at 0.8 and 1.2 of absorbance. The results showed that at 24 hour of exposure at 0.8 and 1.2 of absorbance gave higher degree of adhesion at higher cell concentration. The adhesion of S. aureus and S. cerevisiae on the glass increased by 2.45 % and 2.36 % respectively, at higher cell concentration. Lastly, both S. aureus and S. cerevisiae gave higher percentage of adhesion at stationary phase compared to exponential phase. The percentage of adhesion at exponential state were only 22.9 % and 10.9 % for S. aureus and S. cerevisiae respectively while at stationary state the adhesion were 31.8 % and 21.3 % for respectively